AN ANALYSIS OF A STUDENT’S NARRATIVE TEXT WRITING FROM A SYSTEMIC FUNCTIONAL LINGUISTICS PERSPECTIVE (Lectio: Journal of Language and Language Teaching, 2025)
Narrative text is a text that is designed to entertain the readers. In the Indonesian educationalcontext, the students lack general exposure to how to make an effective narrative text. This studyis aimed at analyzing a student's narrative text. The study participant was a second-grade privateIslamic High School student in Semarang Regency. She was selected as the participant since herwriting showed her as a low achiever, which may portray the whole class's ability. Documentanalysis was employed to obtain adequate information on the student's narrative writing viewedfrom the SFL. The findings indicate that the student lacks grammar, ellipses in finite nominalsentences, L1 interference with word order, and vocabulary mastery. Therefore, to minimize therecurring problems, problem-based learning is one of the best approaches to teaching narrativewriting. It is used since it conveys various activities in which the students are motivated to writeand share their knowledge with others in collaborative learning. Thus, to implement problem?based learning into the teaching and learning process, the steps in teaching problem-basedlearning should be blended into the genre-based approach.
Keywords: narrative texts, genre-based approach, Problem-based learning